Temporality : universals and variation - Bittner, Maria (Chichester, West Sussex, UK : Wiley-Blackwell, 2014)
'Temporality surveys the ways in which languages of different types refer to past, present, and future events, through an in-depth examination of four major language types: tense-based English, tense-aspect-based Polish, aspect-based Chinese, and mood-based Kalaallisut. Cutting-edge research on directly compositional dynamic semantics of languages with and without grammatical tense New in-depth analysis of temporal, aspectual, modal, as well as nominal discourse reference Presents a novel logical language for representing linguistic meaning (Update with Centering) Develops a unified theory of tense, aspect, mood, and person as different types of'grammatical centering systems''--
'Cutting-edge research on directly compositional dynamic semantics of languages with and without grammatical tense'--
Includes bibliographical references (pages 308-317) and indexes.
Print version record and CIP data provided by publisher.
Keywords: Grammar, Comparative and general -- Temporal constructions; Linguistic universals; Language and languages -- Variation; Semantics; Logic, Symbolic and mathematical -- Handbooks, manuals, etc; Natural language processing (Computer science) -- Handbooks, manuals, etc; Semantics -- Handbooks, manuals, etc; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Semantics; Grammar, Comparative and general -- Temporal constructions; Language and languages -- Variation; Linguistic universals; Semantics; Electronic books